IMPLEMENTASI STRATEGI INTEGRASI IMAN DAN PEMBELAJARAN JOHN W. TAYLOR DALAM PEMBELAJARAN MATEMATIKA PADA MATERI BILANGAN [THE IMPLEMENTATION OF JOHN W. TAYLOR'S FAITH AND LEARNING INTEGRATION STRATEGY IN LEARNING MATHEMATICS ON NUMBERS] - Bongga, Steffi Van; Listiani, Tanti (Universitas Pelita Harapan, 2020)
Humans need to receive education in their lives. Through education, humans can develop specifically in intellectual matters. Christian education has the important purpose of introducing God in Bible-based learning. But this only happens if the teacher has implemented biblical integration in learning. One way to do this is through the implementation of John W. Taylor's faith and learning integration strategy. This study focuses specificially on the learning of mathematics in the area of numbers. Christian teachers can truly carry out their call to preach Christ in number mathematics using John W. Taylor's faith and learning integration strategy. This scientific paper is a literature study with supporting data in the form of books, journal articles, and the results of observations and interviews that the author encountered at a Christian school in Ambarawa. This literature review shows that the implementation of John W. Taylor's faith and learning integration strategy in number mathematics can increase students' biblical insights. Students seem to be more enthusiastic learning about knowing God through the learning of number mathematics. It is recommended that teachers implement John W. Taylor strategy with a correct understanding of the steps for its application and make good preparations before teaching.BAHASA INDONESIA ABSTRACT: Manusia perlu menerima pendidikan di dalam kehidupannya. Melalui pendidikan, manusia dapat berkembang terkhusus dalam hal intelektual. Pendidikan Kristen memiliki tujuan yang penting untuk memperkenalkan Allah di dalam pembelajaran yang berlandaskan alkitab. Namun fakta yang terjadi adalah guru belum mengimpelementasikan integrasi alkitabiah di dalam pembelajaran. Salah satu alternatif yaitu melalui implementasi strategi integrasi iman dan pembelajaranJohn W. Taylor. Topik bahasan ini mengarah pada pembelajaran matematika materi bilangan. Tujuan studi literatur ini yaitu agar guru Kristen dapat benar-benar menjalankan panggilannya untuk memberitakan Kristus khusunya di dalam pembelajaran matematika materi bilangan melalui strategi integrasi iman dan pembelajaranJohn W. Taylor. Penulisan studi literatur ini murni kajian literatur dengan data pendukung berupa buku, jurnal, serta hasil observasi dan wawancara yang sesuai dengan persoalan penulis di sekolah Kristen di Ambarawa. Sumber pendukung Kajian literatur ini memperoleh hasil bahwa implementasi strategi integrasi iman dan pembelajaranJohn W. Taylor dalam pembelajaran matematika materi bilangan dapat menambah wawasan alkitabiah siswa. Siswa terlihat lebih antusias mengikuti pembelajaran mengenai pengenalan akan Allah di melalui pembelajaran matematika materi bilangan ini. Disarankan agar guru mengimplementasikan strategi John W. Taylor ini dengan pemahaman yang benar akan langkah-langkah penerapannya serta melakukan persiapan yang baik sebelum mengajar.